A hybrid model of adaptive video streaming control systems - Giuseppe Cofano; Luca De Cicco; Saverio Mascolo (IEEE 55th Conference on Decision and Control (CDC), 2016)
Video streaming traffic over the Internet has significantly grown in the recent years. Adaptive video streaming control systems are employed to provide the best user experience given the user device and the network available bandwidth. The control goal is to maximize the video bitrate while avoiding playback interruptions. In this paper, we present a complete and accurate model of a generic adaptive streaming control system in the form of a hybrid dynamical system. The model describes all the system features, differently from previous models making the fluid-flow approximation, and allows to rigorously design video streaming controllers whose performance can be analytically assessed. The high accuracy of the model has been assessed by comparing numerical simulations to experimental data obtained through real network experiments. Given its accuracy and low computation cost, the proposed model provides a promising alternative to network experiments in order to aid the design and evaluation of adaptive video streaming systems.
Keywords: Streaming media; Bit rate; Adaptive systems; Control systems; Bandwidth; Adaptation models; Internet